Hexavalent vaccine in Peru. Towards safe and sustained coverage of childhood immunization. Expert consensus - Chaparro-Dammert, Luis Eduardo (2020)
Objetive. Immunization is one of the most important interventions to prevent morbidity and mortality in the world population. However, gaps persist to achieve ideal vaccination coverage. In addition, the multiple vaccines and necessary doses make it difficult to reach the minimum established goals. On this scenario, combined and fractionated vaccines are being developed with the aim of reducing the injections number, programmatic errors, reactogenicity and improving adherence.On three different days, for 9 hours, 6 pediatricians experts in vaccines in Peru met following the RAND/UCLA method in order to develop a consensus opinion and update of the combined hexavalent vaccine [DTaP+Haemophilus influenzae type b (Hib)+Hepatitis B (HVB)+Inactivated Polio Vaccine (IPV)] and its eventual use in the Extended Immunization Program (EPI). The consensus recommendation are: replace the vaccines, Oral Polio Vaccine (OPV) by IPV, pertussis of whole cells by acellular vaccines and DTP of 4 years old by dTap between 4 and 6 years old; use the hexavalent vaccine for the primary series (2, 4 and 6 months); use 4 doses of Hib vaccine (2, 4, 6 and 18 months); incorporate the hexavalent vaccine in the EPI; do not use fractionated IPV (fIPV) and only administer 4 doses of IPV.